Pharmacokinetic And Pharmacodynamic Interaction Between Aceclofenac And Rosiglitazone In Rats - R. SATHISH,; J. ANBU,; ASHWINI ANJANA,; K.F.H. NAZEER AHAMED,; G.SRINIVASA RAO, (International Journal of Pharma and Bio Sciences, 2012)
The present study was carried out to investigate the pharmacokinetics and pharmacodynamic interaction of Aceclofenac and Rosiglitazone alone and their combination in rats. The animals were maintained on standard laboratory conditions and were divided into 3 and 6 groups for pharmacokinetic and pharmacodynamic studies respectively. Aceclofenac and Rosiglitazone alone produced antiarthritic and marked reduction in blood glucose levels (Antidiabetic) respectively but their combination produced a decreased efficiency of rosiglitazone for antidiabetic activity and increased antiarthritic activity of aceclofenac when co-administered with Rosiglitazone.